Biological response of cancer cells to radiation treatment - Baskar, Rajamanickam; Dai, Jiawen; Wenlong, Nei; Yeo, Richard; Yeoh, Kheng-Wei (Frontiers in Molecular Biosciences, 2014)
Cancer is a class of diseases characterized by uncontrolled cell growth and has the ability to spread or metastasize throughout the body. In recent years, remarkable progress has been made towards the understanding of proposed hallmarks of cancer development, care and treatment modalities. Radiation therapy or radiotherapy is an important and integral component of cancer management, mostly conferring a survival benefit. Radiation therapy destroys cancer by depositing high-energy radiation on the cancer tissues. Over the years, radiation therapy has been driven by constant technological advances and approximately 50% of all patients with localized malignant tumors are treated with radiation at some point in the course of their disease. In radiation oncology, research and development in the last three decades has led to considerable improvement in our understanding of the differential responses of normal and cancer cells. The biological effectiveness of radiation depends on the linear energy transfer (LET), total dose, number of fractions and radiosensitivity of the targeted cells or tissues. Radiation can either directly or indirectly (by producing free radicals) damages the genome of the cell. This has been challenged in recent years by a newly identified phenomenon known as radiation induced bystander effect (RIBE). In RIBE, the non-irradiated cells adjacent to or located far from the irradiated cells/tissues demonstrate similar responses to that of the directly irradiated cells. Understanding the cancer cell responses during the fractions or after the course of irradiation will lead to improvements in therapeutic efficacy and potentially, benefitting a significant proportion of cancer patients. In this review, the clinical implications of radiation induced direct and bystander effects on the cancer cell are discussed.